INFLUENCE ON SERVICE QUALITY, PRODUCT QUALITY, PRODUCT DESIGN, PRICE AND TRUST TO XL AXIATA CUSTOMER LOYALTY ON STUDENTS OF PGRI KARANG SARI BELITANG III OKU TIMUR VOCATIONAL HIGH SCHOOL - Muhammad Nawawi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2020)
Motivation by business rivalry condition of the telecommunications industry from time to time are getting tight, so the company must create a new marketing strategy to maintain and gain market share higher. As for the problem with this study is "Are service quality, product quality, product design, pricing and trust affect customer loyalty XL Axiata products at the SMK PGRI Karang Sari Belitang III OKU Timur". This study tried to determine the factors that influence consumers make loyalty to the XL Axiata products, especially on students who use the XL Axiata products at the SMK PGRI Karang Sari Belitang III OKU Timur. The purpose of this study to analyze the effect of each - each variable, the quality of product (X1), quality of service (X2), product design (X3), and the price (X) and trust (X5) to customer loyalty (Y). In this study, data were collected through questionnaires to 100 respondents XL Axiata product users in the SMK PGRI Karang Sari Belitang III OKU Timur using purposive sampling method to determine the response of respondents to each variable. Then analyze the data obtained in the form of quantitative analysis and qualitative analysis. Quantitative analysis include validity and reliability test, the classic assumption test, hypothesis testing via the F test and t test and analysis test, the coefficient of determination (R2). Data analysis techniques used were linear regression analysis that serves to prove the research hypothesis. The data that have met the test validity, test reliability, and classical assumption processed so as to produce the following regression equation: Y = 0,274 X1 + 0,218 X2 + 0,270 X3 + 0,238 X4 + 0,207 X5 Results of the analysis found that five factors, product quality , service quality, product design, pricing and the trust has a positive and significant influence on customer loyalty. Hypothesis testing using t test showed that five independent variables found to significantly affect customer loyalty as dependent variables. Then through the F test showed that the variable service quality, product quality, product design, pricing, and the trust has a significant jointly in customer loyalty. Figures adjusted R square of 0.532 indicates that 53.2 percent of the variations of customer loyalty can be explained by five independent variables used in the regression equation. While the rest of 46.8 percent is explained by another variable outside kelimat variables used within this research. Keywords : quality product, service quality, product design, pricing, trust, customer loyalty